Efektifitas Pemberian Permen Jahe dan Kurma Ajwa Terhadap Hypermemesis Gravidarum - Lina Marlina; Ai Rahmawati; Iis Sopiah Suryani; Meti Sulastri; Sri Gustini (Universitas Malahayati Lampung, 2025)
ABSTRACT Pregnancy is often accompanied by changes that cause discomfort, one of which is nausea and vomiting. Excessive nausea and vomiting are known as hyperemesis gravidarum. If not treated properly, it can cause disorders in the mother and fetus. Conventional therapy causes side effects, so a safe natural alternative is needed. The combination of ginger and dates is one form of complementary midwifery care for natural therapy. A more practical and easily accepted alternative is in the form of candy. To determine effectiveness of giving ginger candy and ajwa dates on hyperemesis gravidarum. The type of research used quantitative with a quasi-experimental pretest-posttest one group design. Population in this research was all pregnant women in the first trimester who experienced nausea and vomiting at TPMB E Midwife, with samples by accidental sampling and 15 respondents were obtained. The instrument used was the PUQE-24 (Pregnancy-Unique Quantification of Emesis) questionnaire. Respondents were given ginger candy and ajwa dates with a dose of 2x a day for 7 days. Before and after the intervention, respondents were measured for PUQE. After the data was collected, an analysis was carried out using an independent t-test. Respondent characteristics: the majority of respondents were 20-35 years old as many as 10 people (66.67%), with pariety were primigravida as many as 9 people (60%), with jobs of respondents as housewives as many as 9 people (60%). The PUQE score before the intervention was 9.67, after the intervention the average PUQE score was 6.53. after being analyzed using the dependent t-test, the p value was obtained = 0.000 (0.05). Conclusion: Ginger candy and ajwa dates are effective in reducing nausea and vomiting or hyperemesis gravidarum Keywords: Hyperemesis Gravidarum, Ginger, Ajwa Dates, Nausea and Vomiting ABSTRAK Kehamilan sering disertai banyak perubahan pada tubuh ibu hamil sehingga dapat menimbulkan ketidaknyamanan, salah satunya adalah mual dan muntah. Mual dan muntah yang berlebihan dikenal dengan istilah hyperemesis gravidarum. Butuh penanganan untuk mengurangi gejala yang ada. Jika keadaan ini tidak ditangani dengan baik, maka dapat menyebabkan gangguan yang terjadi baik pada ibu maupun janinnya. Terapi konvensional dengan pengobatan secara farmakologi menimbulkan efek samping, sehingga dibutuhkan alternatif alami yang aman. Kombinasi jahe dan kurma merupakan salah satu bentuk asuhan kebidanan komplementer untuk terapi alami. Alternatif yang lebih praktis dan mudah diterima adalah dalam bentuk permen. Untuk mengetahui Efektifitas pemberian permen jahe dan kurma ajwa terhadap hypermemesis gravidarum. Jenis penelitian menggunakan kuantitatif dengan desain quasi eksperimenpretest-posttest one group. Populasinya adalah seluruh ibu hamil trimester pertama yang mengalami mual muntah di TPMB Bidan E, dengan sampel secara accidental sampling dan diperoleh 15 responden. Instrumen yang digunakan adalah kuesioner PUQE-24 (Pregnancy-Unique Quantification of Emesis). Responden diberi permen jahe dan kurma ajwa dengan dosis 2x sehari selama 7 hari. Sebelum dan sesudah intervensi, responden diukur PUQE. Setelah data terkumpul, dilakukan analisis menggunakan uji t-test independen. Karakteristik responden mayoritas usia 20 – 35 tahun sebanyak 10 orang (66,67%), primigravida sebanyak 9 orang ( 60%), dengan pekerjaan sebagai ibu rumah tangga sebanyak 9 orang ( 60%). Skor PUQE sebelum intervensi sebesar 9.67, setelah intervensi rata-rata skor PUQE adalah 6.53. setelah dianalisis menggunakan uji t-test dependen, didapat nilai p=0.000(0.05). Permen jahe dan kurma ajwa efektif dalam menurunkan mual muntah atau hyperemesis gravidarum Kata Kunci: Hyperemesis Gravidarum, Jahe, Kurma Ajwa, Mual, Muntah